خوارزمية شعاع العناوين متعددة القفزات (AV-MH) لتحديد الموضع في شبكات الحساسات اللاسلكية - خليفة, جمال; البستاني, حسن; عيسى, مهند (Latakia University Journal -Engineering Sciences Series, 2018)
تعتبر عملية تحديد الموضع عملية أساسية في الكثير من تطبيقات الحساسات اللاسلكية كتطبيقات المراقبة البيئية وكشف حرائق الغابات، حيث ترمى الحساسات عشوائيا في الأماكن التي يصعب الوصول اليها، وباعتبار محدودية الحساسات اللاسلكية من حيث الطاقة المتوفرة وقدرة المعالجة تبرز الحاجة إلى خوارزمية غير مكلفة من الناحية المادية ومن ناحية استهلاك الطاقة لتحديد موضع الحساسات.تم في هذا البحث اقتراح خوارزمية جديدة لتحديد موضع تقريبي للحساسات Address Vector Multi Hop (AV_MH)، تعتمد هذه الخوارزمية على فكرة الاستفادة من عملية توزيع العناوين القصيرة في الشبكات التي تدعم العنونة الهرمية باعتبار أن أهم التقنيات المستخدمة في مجال شبكات الحساسات مثل ZigBee 6LowPAN والتي تعتمد المعيار IEEE802.15.4تدعم هذه العنونة. بينت النتائج إمكانية الحصول على موضع تقريبي للحساسات اللاسلكية بطريقة سريعة وغير مكلفة من الناحية المادية ومن ناحية عدد الرسائل المرسلة والحسابات المطلوبة.Localization is an essential process in many wireless sensors Networks applications like environmental surveillance and forest fires detection where sensors usually randomly thrown in difficult to reach places, considering the limited wireless sensors capability in terms of energy availability and the capacity of computations a low cost and energy conservation algorithms are needed to determine the approximate position of the sensors. In this research a new algorithm was proposed ‘Address Vector Multi Hop (AV_MH)’ to determine the position of the randomly deployed sensors, this algorithm is based on the idea of making benefit from short address Assignment in networks that support hierarchical addressing, considering that the most important techniques used in the field of sensor networks such as ZigBee and 6LowPAN which depend on the IEEE802.15.4 standard supports this type of addressing.The results showed the possibility of obtaining an approximate position of the wireless sensors in a rapid and inexpensive and cost effective way in terms of the number of sent messages and required calculations.